Legal entitlements of wives in the classical islamic family law - Yelwa, Mansur Isa; Mohd Zin, Najibah (DISC International, 2015)
This paper addresses the presupposition that without the codified laws of modern Islamic family law, women would end up wandering in pursuance of their legal entitlements in marriage as no concern was given to their rights in the classical law. It proves that such codified laws that protect the conjugal rights of women were extracted from the classical texts of Islamic jurisprudence. Accordingly, the paper brings forth a set of Shari’ah rulings on wives’ rights in the absence of a regulated family law framework for concerned jurisdictions. Textual authorities and juristic dicta are translated, quoted and vividly analyzed comparatively, outlining the diversity of Islamic law within its various Schools of Thought. Legal entitlements covering maintenance, clothing, shelter, sexual relations and other essentials are discussed in depth. Keywords: Classical law; Marriage; Women; Rights; Jurists